2020
DOI: 10.3390/rs12132148
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Modeling with Remotely Sensed Big Data: MODIS Leaf Area Index Improves Hydrology and Water Quality Predictions

Abstract: Traditional watershed modeling often overlooks the role of vegetation dynamics. There is also little quantitative evidence to suggest that increased physical realism of vegetation dynamics in process-based models improves hydrology and water quality predictions simultaneously. In this study, we applied a modified Soil and Water Assessment Tool (SWAT) to quantify the extent of improvements that the assimilation of remotely sensed Leaf Area Index (LAI) would convey to streamflow, soil moisture, and nitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 62 publications
4
22
0
Order By: Relevance
“…Here, we included relevant biophysical parameters during the streamflow calibration process using the aggregated (or lumped) approach (Chen et al, 2017; Cibin et al, 2016; Demissie et al, 2017; Holder et al, 2019). Recent research in watershed modeling has shown improvements in hydrology and water quality predictions with the assimilation of remotely sensed biophysical data (e.g., LAI; Ma et al, 2019; Rajib et al, 2020). Future research is needed to incorporate remotely sensed biophysical parameters in modeling the effect of bioenergy crops on hydrology and water quality with respect to crop yields in various geophysical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we included relevant biophysical parameters during the streamflow calibration process using the aggregated (or lumped) approach (Chen et al, 2017; Cibin et al, 2016; Demissie et al, 2017; Holder et al, 2019). Recent research in watershed modeling has shown improvements in hydrology and water quality predictions with the assimilation of remotely sensed biophysical data (e.g., LAI; Ma et al, 2019; Rajib et al, 2020). Future research is needed to incorporate remotely sensed biophysical parameters in modeling the effect of bioenergy crops on hydrology and water quality with respect to crop yields in various geophysical regions.…”
Section: Discussionmentioning
confidence: 99%
“…The remote sensing literature offers numerous examples proposing earth observation techniques to support assessment of drought conditions [23]. Increasing access to open data, high-resolution remote sensors, and enhanced computing facilities have led to a new set of sophisticated techniques for DEWS in agriculture experiencing drought stress conditions [24], which monitor evapotranspiration [25], soil moisture [26], ground water fluxes [26,27], and precipitation.…”
Section: Dewss Within Food-system Transformationmentioning
confidence: 99%
“…Conversely, Parr et al (2015) found that interannually varying LAI better captured discharge variability and soil moisture estimates. Barbu et al (2011) found that assimilated in situ LAI corrects model deficiencies, particularly during senescence and the start of the growing season, and Rajib et al (2020) assimilated MODIS LAI leading to improved daily streamflow in medium‐to‐low flow conditions and realistic distributions of soil moisture during the growing season. It is the goal of this study to quantify the GVF‐related impacts to land surface fluxes and subsequent runoff within the NWM configuration.…”
Section: Introductionmentioning
confidence: 99%